Mechanisms Underlying Neurodegenerative Disorders and Potential Neuroprotective Activity of Agrifood By-Products - Cristina Angeloni; Marco Malaguti; Cecilia Prata; Michela Freschi; Maria Cristina Barbalace; Silvana Hrelia (MDPI AG, 2022)
Neurodegenerative diseases, characterized by progressive loss in selected areas of the nervous system, are becoming increasingly prevalent worldwide due to an aging population. Despite their diverse clinical manifestations, neurodegenerative diseases are multifactorial disorders with standard features and mechanisms such as abnormal protein aggregation, mitochondrial dysfunction, oxidative stress and inflammation. As there are no effective treatments to counteract neurodegenerative diseases, increasing interest has been directed to the potential neuroprotective activities of plant-derived compounds found abundantly in food and in agrifood by-products. Food waste has an extremely negative impact on the environment, and recycling is needed to promote their disposal and overcome this problem. Many studies have been carried out to develop green and effective strategies to extract bioactive compounds from food by-products, such as peel, leaves, seeds, bran, kernel, pomace, and oil cake, and to investigate their biological activity. In this review, we focused on the potential neuroprotective activity of agrifood wastes obtained by common products widely produced and consumed in Italy, such as grapes, coffee, tomatoes, olives, chestnuts, onions, apples, and pomegranates.